Environmental management of boating related impacts by commercial fishing, sailing and diving tour boat operators in Australia. (16th January 2016) - Byrnes, Troy; Buckley, Ralf; Howes, Michael; Arthur, James M.
Abstract: There are approximately 1500 commercial tour boat operators in Australia with a combined fleet of approximately 3800 vessels – the majority offer marine fishing, sailing or diving tours. Most of the fishing tour boat operators employ fewer staff and use smaller vessels than the dive and sail tour boat operators. Proportionately more of the vessels used by sail and dive tour boat operators have basic environmental management measures such as ashtrays and garbage bins to reduce overboard littering, and sewage holding tanks with pump-out systems to reduce the impacts of human waste. In addition, more of the sail and dive tour boat operators claim to be aware of their boat's environmental impacts and also claim to take steps to reduce or remediate them, including the use of environmental management guidelines. These differences in environmental management measures, however, are associated principally with patterns in vessel size, which affects both the practical and regulatory requirements. In addition, more of the dive tour boat operators operate in marine protected areas (MPAs) where regulations are quite often more stringent. Once these factors are allowed for, environmental management of boating related impacts by individual fishing tour boat operators is not significantly worse than by sail or dive tour boat operators. Overall the attempts to reduce environmental impacts are part of the broader thrust to improve sustainability by ecologically modernising the industry. In this regard, there appears to be significant scope for improvement within the Australian tour boat industry in the form of ensuring that their vessels have garbage bins and ashtrays on board, that such items are clearly labelled and that clients are both advised of their location(s) and the need for their use and especially by clearly advising their clients not to throw items overboard (particularly cigarette butts). Highlights: We examine the environmental management practices of the commercial tour boat sector. We undertake a unique comparison of fish, dive and sail tour industries. We assess the overall effects of an entire industry sector rather than individual members or member groups. We attempt to quantify the overall implications of the environmental management measures in use. We highlight existing management options for mitigation and assess implementation.